The Impact of Hedonic Shopping Motivation and Shopping Lifestyle on Implusive Buying at Lazada (A Study Case in IB It & B Campus Medan) - Yoselin Indrawati (Universitas Muhammadiyah Palu, 2024)
This study aims to see the effect of hedonic shopping motivation, shopping lifestyle on impulsive buying at Lazada for Politeknik UCM students. E-Commerce is one of the most developed business trends in Indonesia currently. The development of the E-Commerce business also occurs in one of the major cities in Indonesia, namely in the city of Medan. People's shopping trends have changed and made the transition to online shopping since the era of the Covid-19 pandemic. The ease of shopping online and the various benefits offered make the development of e-commerce as an online shopping medium increasingly have an increasing development of users This research uses a causal study expecting that the value of the independent variable is the reason for the value of the dependent variable. To prove the hypothesis, the writer uses descriptive method and causal method. The results of this method can be used to prove hypotheses and causation between two or more variables in this study. The coefficient of determination between hedonic shopping motivation and shopping lifestyle on impulsive buying is 0.451. The regression equation is Y = 0.261 + 0.566 X1 + 0.411 X2. The results of descriptive statistics show that the average for hedonic shopping motivation is agree. The results of descriptive statistics show that the average for shopping lifestyle is agree and impulsive buying is neutral. The conclusion from this study is that hedonic shopping motivation has a positive and significant effect on impulsive buying. Shopping lifestyle has a positive and significant effect on impulsive buying. hedonic shopping motivation and shopping lifestyle have a positive and significant effect on impulsive buying.